2022
DOI: 10.7150/thno.71360
|View full text |Cite
|
Sign up to set email alerts
|

Metformin in aging and aging-related diseases: clinical applications and relevant mechanisms

Abstract: Aging is a natural process, which plays a critical role in the pathogenesis of a variety of diseases, i.e., aging-related diseases, such as diabetes, osteoarthritis, Alzheimer disease, cardiovascular diseases, cancers, obesity and other metabolic abnormalities. Metformin, the most widely used antidiabetic drug, has been reported to delay aging and display protective effect on attenuating progression of various aging-related diseases by impacting key hallmark events of aging, including dysregulated nutrient sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 198 publications
0
63
0
1
Order By: Relevance
“…Positive controls were used in the study, Met and NMN. Metformin regulated the insulin and IGF-1 signaling ( 43 ), which were similar effects that SCPs exerted on C. elegans . NMN is a widespread reduction in NAD + that is connected to all of the signs and symptoms of aging.…”
Section: Discussionmentioning
confidence: 88%
“…Positive controls were used in the study, Met and NMN. Metformin regulated the insulin and IGF-1 signaling ( 43 ), which were similar effects that SCPs exerted on C. elegans . NMN is a widespread reduction in NAD + that is connected to all of the signs and symptoms of aging.…”
Section: Discussionmentioning
confidence: 88%
“…When used in some in vivo models, metformin administration increased the lifespan of Caenorhabditis elegans [ 125 , 126 , 127 ] and mice [ 128 , 129 ]. Furthermore, metformin has been reported to benefit patients with cardiovascular diseases [ 130 ] and treat metabolic syndromes and cancer and in the prevention and treatment of aging and aging-related diseases [ 131 , 132 ].…”
Section: Dietary and Nutraceutical Strategies To Tackle Immunosenesce...mentioning
confidence: 99%
“…Metformin was also suggested to have beneficial activity in IDD treatment. This compound was noted to stimulate autophagy, reduce local mechanical hyperalgesia, and inhibit inflammatory responses in NP and AF cells, protecting against apoptosis and senescence [ 79 , 80 ]. An in-depth study performed by Chen et al [ 81 ] concerning its mechanisms of action revealed that metformin activates autophagy in NP cells in a dose- and time-dependent manner, promotes the expression of anabolic genes, such as Col2a1 and Acan , and inhibits the expression of catabolic genes, such as MMP3 and ADAMTS5 .…”
Section: Strategies For Managing Intervertebral Disc Degenerationmentioning
confidence: 99%